2020
DOI: 10.48550/arxiv.2003.07173
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the quantization of the extremal Reissner-Nordstrom black hole

C. Corda,
F. Feleppa,
F. Tamburini

Abstract: Following Rosen's quantization rules, two of the Authors (CC and FF) recently described the Schwarzschild black hole (BH) formed after the gravitational collapse of a pressureless "star of dust" in terms of a "gravitational hydrogen atom". Here we generalize this approach to the gravitational collapse of a charged object, namely, to the geometry of a Reissner-Nordstrom BH (RNBH) and calculate the gravitational potential, the Schrödinger equation and the exact solutions of the energy levels of the gravitational… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Quantization in a larger space through an Eisenhart lift was recently employed in [50]. An analogy between the Schwarzschild-Reissner-Nordström black holes and hydrogen atoms were drawn in [51,52], where their energy spectrum was obtained based on some constructed Schrödinger type equation. A study related to a mass operator and existence of non-zero mass uncertainty can be found here [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…Quantization in a larger space through an Eisenhart lift was recently employed in [50]. An analogy between the Schwarzschild-Reissner-Nordström black holes and hydrogen atoms were drawn in [51,52], where their energy spectrum was obtained based on some constructed Schrödinger type equation. A study related to a mass operator and existence of non-zero mass uncertainty can be found here [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…Bekenstein was the first physicist who observed that, in some respects, BHs play the same role in gravitation that atoms played in the nascent quantum mechanics [1]. This analogy [2] implies that BH energy could have a discrete spectrum [1]. Hence, BHs combine in some sense both the "hydrogen atom" and the "quasithermal" emission in quantum gravity [3].…”
mentioning
confidence: 99%
“…Hence, BHs combine in some sense both the "hydrogen atom" and the "quasithermal" emission in quantum gravity [3]. As a consequence, BH quantization could be the key to a quantum theory of gravity [1][2][3]. Thus, starting from the pioneering works of Bekenstein [4] and Hawking [5], BH quantization became, and currently remains, one of the most important research fields in theoretical physics of the last 50 years.…”
mentioning
confidence: 99%
See 2 more Smart Citations